Production of functional orange juice by the addition of coenzyme Q10 - Goudarzi, Zahra; Hashemiravan, Mahnaz; Sohrabvandi, Sara (Archives of Advances in Biosciences, 2013)
Today, in parallel to growing in acceptance of functional products, various additives are used to improve the characteristics of functional food products. The coenzyme Q10 plays a vital role in cellular energy production. It also increases the body’s immune system via its antioxidant activity. The aim of this study was to evaluate the addition of coenzyme Q10 on physicochemical properties of orange fruit juice. The variables were concentrations of coenzyme Q10 (10 or 20 mg in 300 ml) and storage temperature (25 ° C and 4 ° C) and the parameters were pH, titrable acidity, brix, viscosity, turbidity and sensory evaluation during three months of storage . By increasing time and temperature, pH was decreased and with increasing concentration of coenzyme Q10, pH was increased. Time and temperature had direct influence on acidity, and the concentration of coenzyme Q10 had the opposite effect on the acidity. With increasing storage time and concentration of coenzyme Q10, Brix, viscosity and turbidity levels were increased and with increasing time and concentration of coenzyme Q10, the Brix, viscosity and turbidity were increased. The addition of coenzyme Q10 in grape juice showed no negative effect on the physicochemical and sensory properties.